2011
DOI: 10.1159/000329159
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory-T, T-Helper 1, and T-Helper 2 Cell Differentiation in Nasal Mucosa of Allergic Rhinitis with Olive Pollen Sensitivity

Abstract: Background: Allergic rhinitis (AR) is a disease in which T-helper (Th)2 response is predominant and its pathogenic mechanism is still poorly understood. Aim: To evaluate the possible role of Th1, Th2 and regulatory-T (Treg) cells in the pathogenesis of AR. Methods: This case-control study enrolled 41 patients with seasonal AR (10–62 years old), sensitive to olive pollens, and 15 healthy controls (18–60 years old). Nasal biopsy was performed and specimens of nasal lavage fluid were obtained from all participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…However, the authors did not investigate whether there are functional consequences related to a reduced FoxP3 expression in these cells ( 22 ). In another study, Fontenot et al, found that FoxP3 displayed reduced expression in patients with allergic rhinitis ( 23 ). Because in general, patients with FoxP3 mutations exhibit excessive autoimmunity with high levels of IgE, peripheral eosinophilia and Th2 skewing, the reduced FoxP3 expression may be a contributing factor to the development of allergic diseases in humans ( 24 ).…”
Section: Effector Mechanisms In Allergic Reactionsmentioning
confidence: 97%
“…However, the authors did not investigate whether there are functional consequences related to a reduced FoxP3 expression in these cells ( 22 ). In another study, Fontenot et al, found that FoxP3 displayed reduced expression in patients with allergic rhinitis ( 23 ). Because in general, patients with FoxP3 mutations exhibit excessive autoimmunity with high levels of IgE, peripheral eosinophilia and Th2 skewing, the reduced FoxP3 expression may be a contributing factor to the development of allergic diseases in humans ( 24 ).…”
Section: Effector Mechanisms In Allergic Reactionsmentioning
confidence: 97%
“…Th2 cytokines further suppress Th1 cell differentiation. Ratios of Th1/Th2 and T reg /Th2 are reduced in the nasal mucosa of AR patients during allergen season [ 14 ]. A relative predominance of Th2 cytokine profiles, except for IL-4 levels, was found in nasal fluid of olive-sensitized AR patients compared to healthy controls [ 12 ].…”
Section: Blood Cells In Armentioning
confidence: 99%
“…It is clear that individuals with defective or suboptimal Foxp3 expression due to mutations in Foxp3 gene or in genes that promote Foxp3 expression such as STAT5b are susceptible to allergic diseases [4]. Very recently, it has been noticed that insufficient Treg and Th1 cells may be associated with the allergic inflammation that may be attributed to the Th2 immune response in patients suffering from allergic rhinitis who are sensitive to olive pollen [5]. …”
Section: Introductionmentioning
confidence: 99%